THE STATE'S RESPONSIBILITY TOWARDS THE ELDERLY FAMILY RESILIENCE (A COMPARATIVE STUDY OF INDONESIA, JAPAN, DENMARK) - Uswatun Asiah (Jurnal Analisa Sosiologi, 2025)
The increasing number of elderly people every year is observed in many countries, including Indonesia, and is projected to peak in 2050. The decline in physical function, limited income, and potential social isolation put the elderly at a vulnerable position regarding various problems; therefore, the government must play a role in ensuring welfare through policies implemented through programs. The objective of this research is to analyze the forms of responsibility in maintaining elderly resilience across three countries, from the perspectives of policy and social welfare. This research employs a qualitative approach, utilising literature study methods. The results show that responsibility towards the elderly in Indonesia involves policy-making and the establishment of integrated health posts (posyandu), social assistance, efforts to create age-friendly facilities, and the establishment of elderly schools, while in Japan, there are long-term care insurance (LTCI) programs, onsen facilities, and education on hobbies and in Denmark has a community-based health and social care system, efforts to reduce carbon emissions to create a clean environment, and the development of informal education in the fields of arts, culture, and recreational programs.